Nutritional status and feeding practices among toddlers in selected nurseries in Puncak Alam, Selangor, Malaysia / Naleena Devi Muniandy, Nik Aishah Aliffah Mahdy, Ifrah Ruwaida Mat Saad - Muniandy, Naleena Devi; Mahdy, Nik Aishah Aliffah; Mat Saad, Ifrah Ruwaida (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Nutrition intake and growth during the first five years of life is vital to ensure optimum growth and cognitive development of a child. The National Health and Morbidity Survey in this country indicated that stunting was highest among children 24 to 35 months while overweight was highest among 36 to 47 months, indicating the importance of nutrition assessment in these groups of children. Hence, this study was designed to assess the current growth and nutrition intake and history of feeding practices of the participants. Sixty-seven participants from nine selected nurseries were included in this cross-sectional study. The anthropometry measurements were taken and compared with the WHO growth charts. A three days food diary was used to assess the nutrition intake of the participants. The study revealed that the participants consumed more than twice than the national protein recommendation (boys: 30.7 ± 4.4, and girls 29.7± 5.0) and low calcium intake (boys: 369.7±108.5, girls: 444±51.9). The results also showed a poor history of feeding practices, in which only 25% of the participants were exclusively breastfed until six months and early initiation of solids and semi-solids, as around 25% of the participants were introduced to solids or semi-solids before six months. The results strongly suggest that more initiative needs to be taken to educate mothers on infant and young child feeding practices as nutritional intake and growth during this period are associated with many medical conditions in the future.